I Keep my Problems to Myself: Negative Social Network Orientation, Social Resources, and Health-Related Quality of Life in Cancer Survivors. Issue 3 (22nd December 2015) - Rini, Christine; Symes, Yael; Campo, Rebecca A.; Wu, Lisa M.; Austin, Jane
Abstract: Background: Cancer survivors treated with hematopoietic stem cell transplant rely on their social network for successful recovery. However, some survivors have negative attitudes about using social resources ( negative social network orientation ) that are critical for their recovery. Purpose: We examined the association between survivors' social network orientation and health-related quality of life (HRQoL) and whether it was mediated by social resources (network size, perceived support, and negative and positive support-related social exchanges). Methods: In a longitudinal study, 255 survivors completed validated measures of social network orientation, HRQoL, and social resources. Hypotheses were tested using path analysis. Results: More negative social network orientation predicted worse HRQoL ( p  < .001). This association was partially mediated by lower perceived support and more negative social exchanges. Conclusions: Survivors with negative social network orientation may have poorer HRQoL in part due to deficits in several key social resources. Findings highlight a subgroup at risk for poor transplant outcomes and can guide intervention development.